Struktur Komunitas Ikan Karang Pada Area Transplantasi Terumbu Karang Bagian Selatan Pulau Pagerungan Besar - Nada Fikna Salsabila (Jurnal Serambi Engineering, 2024)
Pagerungan Besar Island is one of the islands in the waters of the Java Sea. Kangean Energy Indonesia Ltd. (KEI) is one of the contractors of SKK MIGAS, carrying out oil and gas exploration and production activities on Pagerungan Besar Island. Based on the results of coral reef monitoring in 2010-2013, the condition of coral reefs in several locations around Pagerungan Besar Island indicated that the percentage of coral reef cover had decreased. The composition of coral fish species found at transplant sites in the southern area consists of 75% large fish, 23% target fish and 14% indicator fish. The number of individual coral fish found reached 1,248 individuals. The most abundant major fish species were from the family Pomancecentridae with 670 individuals, the target fish species were from the family Caesionidae with 266 individuals and the indicator fish were from the family Chaetodontidae with 18 individuals. The diversity value (H') in the medium category is 2.00 - 2.31. This indicates the stability of the ecosystem formed at this site. The uniformity value (E) ranges from 0.55 - 0.65, this value indicates a high uniformity of coral fish species. The dominance value (C) ranges from 0.19 - 0.29, this value indicates that there are no individuals or species of coral fish that dominate at this site.